BENTHIC INVERTEBRATE AT THREE SITES ON THE TIGRIS RIVER, IRAQ (Nativa, 2023)
ABSTRACT: The study was conducted from November 2021 to May 2022 at the three study sites within the Baghdad governorate. The study aims to identify the impact of human activities on the Tigris River, so an area free of human activities was chosen and represented the first site. A total of 48 types were diagnosed, 6204 ind/m3 spread over three sites. The following environmental indicators were evaluated: Constancy Index (S), Relative abundance index (Ra), Richness Index (between 17.995 and 23.251), Shannon Weiner Index (0.48-1.25 bit/ind.), Uniformity Index (0.124 -0.323). The study showed that the highest percentage recorded was for the phylum Annileda 34%; and the stability index shows that taxes (Stylaria sp., Aoelosoma sp., Branchinra sowerby, Chrironomidae sp.) found by 100%, the relative abundance index show that Taxes (Seinura sp. 46% in site 2)(Other nematodes - 43% in site 3; and42% in site 1),(Physa sp. 41% in site 1). The physical and chemical factors were measured BOD between (4.4- 1 mg L-1), DO (10.3-8.3 mg L-1), E.C (893-532 ‰), NO3 (3.12-1 mg L-1), O.M (4.76-1 %), pH (6.8-7.5), PO4 (0.39-0.1 mg L-1), S (0.340-0.571 %), T.H. (321-489 mg L-1), TDS (450-276 mg L-1), Turb (6.3-3.4 mg L-1), C.W. (0.97-0.51 m sec-1), W.T. (13-7 D°).Keywords: environmental monitoring; water quality; aquatic macroinvertebrates. Invertebrados bentônicos em três locais do Rio Tigres, Bagdá, Iraque RESUMO: O estudo foi realizado de novembro de 2021 a maio de 2022, em três locais na província de Bagdá, objetivando identificar o impacto das atividades humanas no Rio Tigre; nesse caso, foi escolhida uma área livre de atividades humanas – representando o ponto de coleta 1. Foram diagnosticados 48 tipos, 6.204 ind/m3 distribuídos em três locais. Foram avaliados os seguintes indicadores ambientais: índice de constância (S), Índice de Abundância Relativa (Ra), Índice de Riqueza entre (17.995-23.251), Shannon Weiner Índice (0,48-1,25 bit/ind.), índice de uniformidade (0,124 -0,323) e índice de estabilidade. O estudo mostrou que o maior percentual registrado foi para o filo Annileda 34%; e o índice de estabilidade mostra que os macroinvertebrados  (Stylaria sp., Aoelosoma sp., Branchinra sowerby, Chrironomidae sp.) encontrados em 100%, o índice de abundância relativa mostra que os impostos (Seinura sp. 46%, no local 2) (Outros nematóides - 43 % no local 3; e 42% no local 1),(Physa sp. 41% no local 1). Os fatores físicos e químicos medidos apresentaram os seguintes resultados: BOD entre (4.4- 1 mg L-1), DO (10.3-8.3 mg L-1), E.C (893-532 ‰), NO3 (3.12-1 mg L-1), O.M (4.76-1 %), pH (6.8-7.5), PO4 (0.39-0.1 mg L-1), S (0.340-0.571 %), T.H. (321-489 mg L-1), TDS (450-276 mg L-1), Turb (6.3-3.4 mg L-1), C.W. (0.97-0.51 m sec-1), W.T. (13-7 D°).Palavras-chave:  monitoramento ambiental; qualidade da água; macroinvertebrados aquáticos.